A critical look at the various methods of teaching law / John Chuah Chong Oon - John, Chuah Chong Oon (Institute of Quality & Knowledge Advancement (InQKA), 2005)
The purpose of this paper is to explore the various conventional methods of teaching law in respect of its strength and shortcomings. The question of which is the superior method of teaching law naturally arises in view of the fact UiTM has targeted itself to be a world class university by the year 2006. Teaching, writing and research are after all the bread and butter of every lecturer and to attain or maintain world-class standards, several questions on the methodology of teaching law will be addressed. Several issues would also be discussed along the way. In particular the writer seeks to argue that there may be a distinct difference in teaching law to non law students who are studying law as a single (or two) subject; compared with full fledged law students. Hence should pragmatism in teaching law prevail over idealism, that is should we teach students with the primary emphasis to pass exams or to face the challenges of working life via development of professional skills bearing in mind a university paper qualification is no guarantee of success in the working life? Lastly what should be the strife of the law lecturer as he/she endeavors to continue to improve himself/herself as a lecturer besides the acquisition of knowledge?